A new species of freshwater crab of the genus Chaceus Pretzmann, 1965 (Brachyura: Decapoda: Pseudothelphusidae) from La Guajira, including distribution and a key to the species of the genus - Campos, Martha R.; Puerta, Dario A. (Zootaxa, 2023)
We describe and illustrate a new species of Chaceus Pretzmann, 1965, from the Regional Natural Park of the Serranía de Perijá, La Guajira Department, Colombia. This increases the number of Chaceus species to ten, three of them with records only from Venezuela. The species of this genus are distributed in the Sierra de Santa Marta of Colombia and the Serranía de Perijá of Colombia and Venezuela. We distinguished the new species from its congeners mainly by the third maxilliped, with an exopod that is 0.60–0.62 the length of ischium, and by the morphology of the first male gonopod, particularly by the shapes of the mesial, marginal, and lateral processes. We include the distribution of the Chaceus species here and a key for the identification of the species based on the morphology of the first male gonopod.